On The Realization of Simulated Lossy Inductors Using Voltage Differencing Buffered Amplifiers - Moonmuang, Pitchayanin; Roongmuanpha, Natchanai; Pukkalanun, Tattaya; Tangsrirat, Worapong (My University, 2020)
This paper reports four topologies, all simulating floating/grounded lossy inductors, using voltage differencing buffered amplifiers (VDBAs) as active elements. The simulated equivalent resistance and inductance values of the simulators can be adjusted electronically through the VDBA transconductance parameter. Non-ideal gain outcomes of the VDBA on the realized inductor circuits are finalized. The critical active and passive sensitivities are obtained to be low.
Keywords: electronically tunable; inductance simulator; lossy inductor; Voltage Differencing Buffered Amplifier (VDBA)